2009
DOI: 10.1007/s11094-010-0381-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid determination of the identity of aqueous drug solutions

Abstract: The stationary stability of giant heterophase clusters (GHCs) of water in samples of sodium chloride isotonic aqueous solutions from three manufacturers has been studied. The influence of the NaCl concentration on the relaxation kinetics of GHCs is established. A method for determining the identity of aqueous drug solutions without violating the integrity of the packaging is developed.Key words: giant heterophase clusters (GHCs) of water, sodium chloride isotonic solution, identity of aqueous drug solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In the pharmaceutical industry, various approaches are used to increase the solubility of APIs: micronization, modification of the crystal structure, salt formation, preparation of solid dispersions, self-nanoemulsifying drug delivery system, mechanochemical synthesis and others [28][29][30]. In recent studies it was found that the physicochemical and biological properties of AРI aqueous solutions -the mutarotation rates, the angle of optical rotation, the lifetime of the cell biosensor are dependent on the D/H ratios [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In the pharmaceutical industry, various approaches are used to increase the solubility of APIs: micronization, modification of the crystal structure, salt formation, preparation of solid dispersions, self-nanoemulsifying drug delivery system, mechanochemical synthesis and others [28][29][30]. In recent studies it was found that the physicochemical and biological properties of AРI aqueous solutions -the mutarotation rates, the angle of optical rotation, the lifetime of the cell biosensor are dependent on the D/H ratios [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The method has successfully proven itself in assessing the quality of liquid dosage forms: suspensions, emulsions, tinctures, and determining the authenticity of medicinal and table waters without opening the package, as well as the stability of cluster structures in waters of different isotopic composition (Bunkin et al, 2018;Goncharuk et al, 2011;Karpov et al, 2011;Koldina et al, 2019;Ul'yantsev et al, 2009). Reliability of measurements, nondestructive nature, low cost, simplicity of calibration procedures, and short measurement times are important advantages of the method in the analysis of pharmaceutical substances.…”
Section: Introductionmentioning
confidence: 99%